Knowledge, Awareness And Perceptions Of Females On Clandestine Abortion In Kintampo North Municipality, Ghana - Alhassan, Alhassan Yakubu; Abdul-Rahim, Abdulai; Akaabre, Paul Boniface (European Scientific Journal, ESJ, 2016)
Clandestine Abortion will continue to be an integral part of human society as long as people continue to accept and engage in sexual activities without being prepared to give birth. Despite the risks (death and other health complication) involved in clandestine abortion, people continue to engage in the act. The central inquiry is; why do people continue to do clandestine abortions despite its associated risk? Do people have knowledge on abortion concerning its legalities and associated risks? This paper thus seeks to clarify the above questions by examining the knowledge, awareness and perceptions of females on abortion, with focus on clandestine abortion in the Kintampo North Municipality of Ghana. The paper reveals that, though most females have little knowledge on the 1985 abortion law, they are aware of the risks associated with criminal abortion. Despite being aware of the risks, circumstances such as unwanted pregnancies, poverty, desire to pursue education and career goals, and job related issues compel most to abort pregnancies through dangerous means. The paper therefore calls for public education on abortion laws in Ghana to be intensified and possibly, consider shifting the existing paradigms of the abortion law in order to curb clandestine abortions and its associated fatalities.